Molecular targeted therapies in adrenal, pituitary and parathyroid malignancies. Issue 6 (June 2017) - Angelousi, Anna; Dimitriadis, Georgios K; Zografos, Georgios; Nölting, Svenja; Kaltsas, Gregory; Grossman, Ashley
Abstract : Tumourigenesis is a relatively common event in endocrine tissues. Currently, specific guidelines have been developed for common malignant endocrine tumours, which also incorporate advances in molecular targeted therapies (MTT), as in thyroid cancer and in gastrointestinal neuroendocrine malignancies. However, there is little information regarding the role and efficacy of MTT in the relatively rare malignant endocrine tumours mainly involving the adrenal medulla, adrenal cortex, pituitary, and parathyroid glands. Due to the rarity of these tumours and the lack of prospective studies, current guidelines are mostly based on retrospective data derived from surgical, locoregional and ablative therapies, and studies with systemic chemotherapy. In addition, in many of these malignancies the prognosis remains poor with individual patients responding differently to currently available treatments, necessitating the development of new personalised therapeutic strategies. Recently, major advances in the molecular understanding of endocrine tumours based on genomic, epigenomic, and transcriptome analysis have emerged, resulting in new insights into their pathogenesis and molecular pathology. This in turn has led to the use of novel MTTs in increasing numbers of patients. In this review, we aim to present currently existing and evolving data using MTT in the treatment of adrenal, pituitary and malignant parathyroid tumours, and explore the current utility and effectiveness of such therapies and their future evolution.